Post-Soviet Central Asia in the Focus of Interests of Major Asian States (2019-2020) - D. B. Malysheva (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2021)
The study aims at identifying some areas of international political interaction between post-Soviet Central Asian states and the major economic powers of Asia -China, India and Japan. The task is to determine their interests in the Central Asian region with an emphasis on the political component. The current state of political cooperation between China, India, Japan and the countries of Central Asia is considered. Their joint efforts to solve the problems and threats facing the sustainable development of the region are characterized, while overcoming those problems occurs within the framework of the formation of both bilateral and multilateral relations. The dynamics of political and military interaction between China and its Central Asian partners is revealed. It is shown that the regional security sphere is directly linked by China with the problem of protecting its own economic interests in the countries undergoing its Belt and Road program, aimed at changing the economic landscape not only in Central Asia, but throughout Asia. India and Japan, whose positions have come closer against the background of rising China, has defined their own strategies for Central Asia. Politics of major Asian powers in post-Soviet Central Asia are analyzed through the prism of the emergence of a polycentric world in Asia. Its distinctive features are: the emergence of new regional “centers of power”; their confrontation along the line of Sino-Pakistani, Sino-Indian rivalries; involvement of external players (the U.S.) in regional processes. In this regard, attention is drawn to the activities of such a multilateral international structure as the Shanghai Cooperation Organization (SCO), as well as to the development of alternative infrastructure projects and concepts - QUAD, Indo-Pacific, Blue Dot Network. The results of the study are formulated in the following conclusion: the countries of Central Asia and the major regional economic powers in Asia base their relations on the foundation of mutually beneficial interests and equal partnership of independent states.